GetPasar Enterprise / Nur Anis Amalin Mohd Hishamuddin - Mohd Hishamuddin, Nur Anis Amalin (2021)
The report below is the report about a case study that requires me to do survey about entrepreneur and his competencies. In this case study, the founder and the owner of GetPasar, named Wan Nazaruddin Bin Wan Hussin. He is the fourth child of seven siblings. This company was created because of pandemic COVID-19. He was a pilot but since he cannot fly, he created GetPasar to gain income and help people to buy the groceries around Kuala Lumpur and Selangor. The type of business is sole proprietorship. We had interview session through WhatsApp application and the session went very smoothly. On November 8, 2020, GetPasar Enterprise was founded. Wan Nazaruddin Bin Wan Hussin, the founder, came up with the concept for GetPasar after struggling to make ends meet at his current profession as a pilot. COVID-19 caused a pandemic that affected the entire planet in 2020. Through the interview session, I get to collect all the information I need. Wan Nazaruddin very friendly as he gave all details about his business. From my case study, I get to determine which entrepreneurial competencies that Wan Nazaruddin have. Wan Nazaruddin Bin Hussin have three entrepreneurial competencies that he practice in his business.